Managing supply chain a logistics approach - Dolan, Porter (Clanrye International, 2017)
Supply chains are a visualization of the movement of goods from producer to consumer. This book on managing supply chains discusses the various components that comprise supply chains. Proper handling of material, packaging, transportation and warehousing is a significant aspect of supply chain management. This book is a vital tool for all researching and studying this field. Topics included in this book deal with the efficient usage of supplies. The aim of this text is to present researches that have transformed this discipline and aided its advancement. As this field is emerging at a fast pace, this book will help the readers to better understand the concepts of supply chain management. With state-of-the-art inputs by acclaimed experts of this field, this book targets students and professionals.